2022
DOI: 10.18502/tim.v7i2.9917
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ear Acupressure on Back Pain after Coronary Angiography: A Randomized Controlled Trial

Abstract: Back pain is a common complaint seen in patients after coronary angiography. This study investigated the efficacy of ear acupressure for reduction of back pain in patients after coronary angiography. In this trial, 120 patients recruited from a post-angiography ward were allocated to an ear acupressure or a control group. Pain assessment in intervention group was performed immediately after participants entered post- coronary angiography ward (T0), twenty minutes after entering the ward (T1), and two, four, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…As illustrated in Figure 2, all nine studies [5,14,[19][20][21][22][23][24][25] achieved a high level of quality.…”
Section: │ Methodological Quality Assessment Of Eligible Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…As illustrated in Figure 2, all nine studies [5,14,[19][20][21][22][23][24][25] achieved a high level of quality.…”
Section: │ Methodological Quality Assessment Of Eligible Studiesmentioning
confidence: 99%
“…A detailed examination of the full texts of fifty-two studies revealed that thirty-one studies were deemed inadequate in terms of design and findings, while twelve studies lacked essential data. Ultimately, nine studies [5,14,[19][20][21][22][23][24][25] met the inclusion criteria and were included in this systematic review.…”
Section: │ Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations